Comparative Literature: Theory, Method, Application - Zepetnek, Steven Tötösy de, (Literature and Cultural Studies - Book Archive pre-2000, 1998)
This book serves several purposes, all very much needed in today's embattled situation of the humanities and the study of literature. First, in Chapter One, the author proposes that the discipline of Comparative Literature is a most advantageous approach for the study of literature and culture as it is a priori a discipline of cross-disciplinarity and of international dimensions. After a Manifesto for a New Comparative Literature, he proceeds to offer several related theoretical frameworks as a composite method for the study of literature and culture he designates and explicates as the systemic and empirical approach. Following the introduction of the proposed New Comparative Literature, the author applies his method to a wide variety of literary and cultural areas of inquiry such as Literature and Cultural Participation where he discusses several aspects of reading and readership (Chapter Two), Comparative Literature as/and Interdisciplinarity (Chapter Three) where he deals with theory and application for film and literature and medicine and literature, Cultures, Peripheralities, and Comparative Literature (Chapter Four) where he proposes a theoretical designation he terms inbetween peripherality for the study of East Central European literatures and cultures as well as ethnic minority writing, Women's Literature and Men Writing about Women (Chapter Five) where he analyses texts written by women and texts about women written by men in the theoretical context of Ethical Constructivism, The Study of Translation and Comparative Literature (Chapter Six) where after a theoretical introduction he presents a new version of Anton Popovic's dictionary for literary translation as a taxonomy for the study of translation, and The Study of Literature and the Electronic Age (Chapter Seven), where he discusses the impact of new technologies on the study of literature and culture. The analyses in their various applications of the proposed New Comparative Literature involve modern and contemporary authors and their works such as Dorothy Richardson, Margit Kaffka, Mircea Cartarescu, Robert Musil, Alfred Döblin, Hermann Hesse, Péter Esterházy, Dezsö Kosztolányi, Michael Ondaatje, Endre Kukorelly, Else Seel, and others.